2022
DOI: 10.1186/s13195-022-01093-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of plasma p-tau181, NfL, and GFAP in a clinical setting cohort of prevalent neurodegenerative dementias

Abstract: Background Increasing evidence supports the use of plasma biomarkers of neurodegeneration and neuroinflammation to screen and diagnose patients with dementia. However, confirmatory studies are required to demonstrate their usefulness in the clinical setting. Methods We evaluated plasma and cerebrospinal fluid (CSF) samples from consecutive patients with frontotemporal dementia (FTD) (n = 59), progressive supranuclear palsy (PSP) (n = 31), corticoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 57 publications
(57 reference statements)
3
60
1
Order By: Relevance
“…The performance of plasma markers to discriminate patients with AD from cognitively unimpaired participants, patients with other dementias and with not degenerative dementias has been assessed in previous studies using other analytical platforms, with AUCs ranging from 0.70 to 0.96 for pTau 181 [7,17,[23][24][25][26][27], and from 0.64 to 0.86 for Aβ 1-/Aβ 1-40 [5,8,10]. Most of the studies reported better accuracies with the use of composite measures that combined two or more markers and/or clinical or genetic information.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of plasma markers to discriminate patients with AD from cognitively unimpaired participants, patients with other dementias and with not degenerative dementias has been assessed in previous studies using other analytical platforms, with AUCs ranging from 0.70 to 0.96 for pTau 181 [7,17,[23][24][25][26][27], and from 0.64 to 0.86 for Aβ 1-/Aβ 1-40 [5,8,10]. Most of the studies reported better accuracies with the use of composite measures that combined two or more markers and/or clinical or genetic information.…”
Section: Discussionmentioning
confidence: 99%
“…2 Biomarker evidence consistent with AD in the previous study required at least one modality of an abnormal amyloid marker, but not tau measure, [3][4][5] or defined based on differentiating between clinical diagnosis of AD and controls. 6,7 However, the limitation of the former is that individuals with only abnormal amyloid pathology may not have AD because some individuals who had ante mortem abnormal amyloid markers but normal tau markers were not found to have AD at autopsy. 8 The limitation of the latter is that clinical diagnosis may not be consistent with the pathological diagnosis and may not accurately reflect the presence of AD neuropathology.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, reliable assays that can detect p-tau and NfL in blood have become available, paving the way for more widespread use of these biomarkers in clinical practice 7 8. In particular, the measurement of blood p-tau is increasingly considered a realistic, cost-effective and non-invasive assay that will help the diagnostic process for patients with cognitive decline 7 9 10. Nevertheless, whether plasma measures of these biomarkers exclusively reflect their cerebrospinal fluid (CSF) concentration or are also influenced by peripheral sources remains to be fully explored.…”
Section: Introductionmentioning
confidence: 99%